Religious pluralism in South Asia and Europe - Malik, Jamal; Reifeld, Helmut (New Delhi : Oxford University Press, 2005)
Contributed articles.
Keywords: RELIGIOUS PLURALISM -- INDIA; RELIGIOUS PLURALISM -- SOUTH ASIA